A Novel Hybrid Machine Learning Classifier-Based Digital Differential Protection Scheme for Intertie Zone of Large-Scale Centralized DFIG-Based Wind Farms - Rezaei N.; Uddin M.N.; Amin I.K.; Othman M.L.; Marsadek M.B.; Hasan M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Asynchronous generators; Clustering algorithms; E-learning; Electric equipment protection; Electric fault currents; Electric power system interconnection; Electric power system protection; Electric transformers; Electric utilities; Learning systems; Storms; Support vector machines; Wind; Wind power; Differential protection; Doubly fed induction generators; Dynamic behaviors; Hybrid machine learning; Impedance measurement; Laboratory environment; Renewable energies; Supervised machine learning; Electric power transmission networks